Pharmacologic and clinical evaluation of posaconazole - Moore, Jason N (Expert Rev Clin Pharmacol, 2015)
Posaconazole, a broad-spectrum triazole antifungal agent, is approved for the prevention of invasive aspergillosis and candidiasis in addition to the treatment of oropharyngeal candidiasis. There is evidence of efficacy in the treatment and prevention of rarer, more difficult-to-treat fungal infections. Posaconazole oral suspension solution has shown limitations with respect to fasting state absorption, elevated gastrointestinal pH and increased motility. The newly approved delayed-release oral tablet and intravenous solution formulations provide an attractive treatment option by reducing interpatient variability and providing flexibility in critically ill patients. On the basis of clinical experience and further clinical studies, posaconazole was found to be a valuable pharmaceutical agent for the treatment of life-threatening fungal infections. This review will examine the development history of posaconazole and highlight the most recent advances.